Veliparib with carboplatin and paclitaxel in BRCA-mutated advanced breast cancer (BROCADE3): a randomised, double-blind, placebo-controlled, phase 3 trial - Diéras, Véronique; Han, Hyo S; Kaufman, Bella; Wildiers, Hans; Friedlander, Michael; Ayoub, Jean-Pierre; Puhalla, Shannon L; Bondarenko, Igor; Campone, Mario; Jakobsen, Erik H; Jalving, Mathilde; Oprean, Cristina; et al. (The Lancet. Oncology, 2020)
BACKGROUND: BRCA1 or BRCA2-mutated breast cancers are sensitive to poly(ADP-ribose) polymerase (PARP) inhibitors and platinum agents owing to deficiency in homologous recombination repair of DNA damage. In this trial, we compared veliparib versus placebo in combination with carboplatin and paclitaxel, and continued as monotherapy if carboplatin and paclitaxel were discontinued before progression, in patients with HER2-negative advanced breast cancer and a germline BRCA1 or BRCA2 mutation. METHODS: BROCADE3 was a randomised, double-blind, placebo-controlled, phase 3 trial done at 147 hospitals in 36 countries. Eligible patients (aged ≥18 years) had deleterious germline BRCA1 or BRCA2 mutation-associated, histologically or cytologically confirmed advanced HER2-negative breast cancer, an Eastern Cooperative Oncology Group performance status of 0-2, and had received up to two previous lines of chemotherapy for metastatic disease. Patients were randomly assigned (2:1) by interactive response technology by means of permuted blocks within strata (block size of 3 or 6) to carboplatin (area under the concentration curve 6 mg/mL per min intravenously) on day 1 and paclitaxel (80 mg/m2 intravenously) on days 1, 8, and 15 of 21-day cycles combined with either veliparib (120 mg orally twice daily, on days -2 to 5) or matching placebo. If patients discontinued carboplatin and paclitaxel before progression, they could continue veliparib or placebo at an intensified dose (300 mg twice daily continuously, escalating to 400 mg twice daily if tolerated) until disease progression. Patients in the control group could receive open-label veliparib monotherapy after disease progression. Randomisation was stratified by previous platinum use, history of CNS metastases, and oestrogen and progesterone receptor status. The primary endpoint was investigator-assessed progression-free survival per Response Evaluation Criteria in Solid Tumors version 1.1. Efficacy analyses were done by intention to treat, which included all randomly assigned patients with a centrally confirmed BRCA mutation, and safety analyses included all patients who received at least one dose of velilparib or placebo. This study is ongoing and is registered with ClinicalTrials.gov, NCT02163694. FINDINGS: Between July 30, 2014, and Jan 17, 2018, 2202 patients were screened, of whom 513 eligible patients were enrolled and randomly assigned. In the intention-to-treat population (n=509), 337 patients were assigned to receive veliparib plus carboplatin-paclitaxel (veliparib group) and 172 were assigned to receive placebo plus carboplatin-paclitaxel (control group). Median follow-up at data cutoff (April 5, 2019) was 35·7 months (IQR 24·9-43·6) in the veliparib group and 35·5 months (23·1-45·9) in the control group. Median progression-free survival was 14·5 months (95% CI 12·5-17·7) in the veliparib group versus 12·6 months (10·6-14·4) in the control group (hazard ratio 0·71 [95% CI 0·57-0·88], p=0·0016). The most common grade 3 or worse adverse events were neutropenia (272 [81%] of 336 patients in the veliparib group vs 143 [84%] of 171 patients in the control group), anaemia (142 [42%] vs 68 [40%]), and thrombocytopenia (134 [40%] vs 48 [28%]). Serious adverse events occurred in 115 (34%) patients in the veliparib group versus 49 (29%) patients in the control group. There were no study drug-related deaths. INTERPRETATION: The addition of veliparib to a highly active platinum doublet, with continuation as monotherapy if the doublet were discontinued, resulted in significant and durable improvement in progression-free survival in patients with germline BRCA mutation-associated advanced breast cancer. These data indicate the utility of combining platinum and PARP inhibitors in this patient population. FUNDING: AbbVie.
Keywords: Drug-Related Side Effects and Adverse Reactions; Humans; lidé středního věku; Double-Blind Method; Benzimidazoles; Drug Administration Schedule; zárodečné mutace; Carboplatin; Female; dospělí; protokoly protinádorové kombinované chemoterapie; výsledek terapie; dvojitá slepá metoda; nežádoucí účinky léčiv; lidé; PARP inhibitory; doba přežití bez progrese choroby; benzimidazoly; Genes, BRCA2; Poly(ADP-ribose) Polymerase Inhibitors; Adult; Breast Neoplasms; Genes, BRCA1; geny BRCA1; Germ-Line Mutation; ženské pohlaví; Middle Aged; paclitaxel; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; nádory prsu; organoplatinové sloučeniny; Progression-Free Survival; Paclitaxel; karboplatina; geny BRCA2; Organoplatinum Compounds; rozvrh dávkování léků